2021
DOI: 10.1093/mnras/stab1822
|View full text |Cite
|
Sign up to set email alerts
|

Redshift-space distortions in simulations of the 21-cm signal from the cosmic dawn

Abstract: The 21-cm signal from the Cosmic Dawn (CD) is likely to contain large fluctuations, with the most extreme astrophysical models on the verge of being ruled out by observations from radio interferometers. It is therefore vital that we understand not only the astrophysical processes governing this signal, but also other inherent processes impacting the signal itself, and in particular line-of-sight effects. Using our suite of fully numerical radiative transfer simulations, we investigate the impact on the redshif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 94 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that with SKA-Low, such an observation time will yield a sufficient signal-to-noise ratio (SNR) to study the properties of cosmic dawn [e.g. 2,62,74,77,82,88]. We furthermore assume a bandwidth of 10 MHz.…”
Section: A Mock Observationsmentioning
confidence: 99%
“…Previous studies have shown that with SKA-Low, such an observation time will yield a sufficient signal-to-noise ratio (SNR) to study the properties of cosmic dawn [e.g. 2,62,74,77,82,88]. We furthermore assume a bandwidth of 10 MHz.…”
Section: A Mock Observationsmentioning
confidence: 99%
“…Lastly, we did not include redshift space distortions or the light cone effect, which have both been shown to alter the shape of the 21-cm power spectrum (e.g. Barkana & Loeb 2006;Mao et al 2012;Datta et al 2012;Mondal et al 2018;Ross et al 2021). However, a preliminary check showed no major changes to the evolution of the decomposition when redshift space distortions were included.…”
Section: Generality Of the Decompositionmentioning
confidence: 99%
“…By definition, the power spectrum provides the auto-correlation between the signal at a single Fourier mode and thus cannot capture this non-Gaussianity. The fundamental statistics which can capture this non-Gaussianity are skewness and kurtosis [21,[49][50][51][52][53][54]. However, these statistics can only probe the non-Gaussian features at a single length scale.…”
Section: Introductionmentioning
confidence: 99%